Homogeneous chip to wafer bonding of InP-Al2O3-Si using UV/O3 activation - Tan, Chuan Seng (2014)
A direct chip to wafer bonding of indium phosphide (InP) onto silicon using Al2O3 as the intermediate homogenous bonding layer is reported. Intermediate film thickness is varied from 5 to 20 nm and the UV/O3 activation time is optimized to result in minimal surface roughness and contact angle required for effective direct wafer bonding. TEM characterization of the interface reveals a homogeneously fused Al2O3 layer. In addition Al2O3 is shown to best emulate the thermal characteristics of direct InP/Si bonding as compared to using SiO2 as the interfacial bonding layer. Therefore Al2O3 is recognized be a highly competent interfacial layer for chip to wafer bonding for integrated photonic application.